Research article interval network analysis in project management - S, Radhakrishnan; D, Saikeerthana (Kongunadu Research Journal, 2020)
This paper deals with an analysis of Critical Path Method (CPM) and Programme Evaluation Review Technique (PERT) in Project Network. Here, we solve the PERT and CPM methodology using intervals and we determine the critical path and project duration of the network. We can also convert the fuzzy parameters (triangular and trapezoidal fuzzy numbers) into intervals using α − cuts. After which, we calculate the project duration and critical path. To illustrate this, numerical examples are provided.